Restrição alimentar em caprinos: rendimento, cortes comerciais e composição da carcaça - Yáñez, Enrique Alejandro; Resende, Kleber Tomás de [UNESP]; Ferreira, Ângela Cristina Dias; Pereira Filho, José Morais; Silva Sobrinho, Américo Garcia da [UNESP]; Teixeira, Izabelle Auxiliadora Molina de Almeida [UNESP]; Medeiros, Ariosvaldo Nunes de (Sociedade Brasileira de Zootecnia, 2006)
Com o objetivo de estudar o efeito da restrição alimentar sobre as características da carcaça de caprinos leiteiros, realizou-se um experimento utilizando 27 cabritos castrados da raça Saanen. Os animais (PV inicial de 20 kg) foram distribuídos nos tratamentos alimentação à vontade e 30 e 60% de restrição, sendo abatidos aos 35 kg de PV. Foram avaliados o rendimento comercial e biológico, os cortes comerciais, a área de olho-de-lombo e a composição tecidual da perna. O rendimento biológico não foi afetado pela restrição alimentar, mas o comercial diminuiu com o aumento da restrição. A elevação no nível de restrição alimentar promoveu diminuição do lombo e da 6ª a 13ª costelas e aumento da paleta e do pescoço, proporcionalmente à meia-carcaça. A proporção de ossos aumentou e a de gordura total diminuiu com o aumento da restrição. O tecido muscular não foi afetado pela restrição. A restrição alimentar de até 30% não prejudicou a qualidade da carcaça de caprinos leiteiros.

Twenty-seven Saanen male kids averaging 20 kg of body weight (BW) at the beginning of the trial were used to study the effects of feed restriction on carcass characteristics. Animals were assigned to one of the following three treatments: control (fed ad libitum), 30 or 60% of feed restriction. A completely randomized design was used and data were submitted to regression analysis; animals were slaughtered when they reached 35 kg of BW. The following traits were measured in this trial: carcass commercial and biological yields, commercial cuts, tissue composition of hind leg, rib eye area (REA), and carcass compactness. Increasing feed restriction reduced carcass and commercial cut weights as well as loin and fat proportions in the carcass. Conversely, proportions of bone, neck, and shoulder clod all increased when the feed restriction went from 0 to 60%. Muscle tissue proportion was not changed by feed restriction in this study. It can be concluded that 30% of feed restriction did not negatively affected carcass quality of Saanen dairy kids.
Feed restriction in goats: carcass yield, commercial cuts, and carcass composition
Keywords: castrated kids; commercial yield; Fat; Muscle; tissue composition; cabritos castrados; Composição tecidual; Gordura; músculo; rendimento comercial